2020
DOI: 10.1186/s12984-020-00746-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive robot-assisted rehabilitation of hand function: a randomized control trial on motor recovery in subacute stroke

Abstract: Background: Hand function is often impaired after stroke, strongly affecting the ability to perform daily activities. Upper limb robotic devices have been developed to complement rehabilitation therapy offered to persons who suffered a stroke, but they rarely focus on the training of hand sensorimotor function. The primary goal of this study was to evaluate whether robot-assisted therapy of hand function following a neurocognitive approach (i.e., combining motor training with somatosensory and cognitive tasks)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 64 publications
2
44
0
12
Order By: Relevance
“…Several rehabilitation measures, such as robotic rehabilitation therapy and mirror therapy, have been reported to be effective in improving hand function of stroke survivors with severe sequelae. 16 , 17 Apart from their individual impact, research shows that exercise enhances the effect of stem cells by helping the mobilization of local stem cells and encouraging angiogenesis. Hence, the concept of neuroregenerative rehabilitation therapy (NRRT) is becoming a potential research direction in the hope of finding a more effective approach to treat stroke sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Several rehabilitation measures, such as robotic rehabilitation therapy and mirror therapy, have been reported to be effective in improving hand function of stroke survivors with severe sequelae. 16 , 17 Apart from their individual impact, research shows that exercise enhances the effect of stem cells by helping the mobilization of local stem cells and encouraging angiogenesis. Hence, the concept of neuroregenerative rehabilitation therapy (NRRT) is becoming a potential research direction in the hope of finding a more effective approach to treat stroke sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…During these telerehabilitation sessions, the occupational therapist will give the patient the necessary instructions to perform various exercises. First, a prior physical warm-up, consisting of a series of mobility exercises and stretching, followed by exercises designed to improve body posture, increase mobility, favor transfers, reduce axial stiffness, freezing, and walking disturbances, and enhancing balance and coordination, according to the cognitive, sensory-motor training therapy (Perfetti method) [ 28 , 29 ]. During this cognitive sensory-motor training therapy, motor control will be improved using a specific type of repetitive sensory and motor re-learning protocol.…”
Section: Methodsmentioning
confidence: 99%
“…During this cognitive sensory-motor training therapy, motor control will be improved using a specific type of repetitive sensory and motor re-learning protocol. Different exercises will be accommodated based on the patient’s capacity, including kinesthetic tasks [simple to complex parameter movement discrimination] with the corresponding cognitive activity [recognition of the direction and distance of the movement], and coordination tasks associated with executive cognitive activity [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite RAT allowing the recovery process of impaired functions, more controlled and randomized clinical trials are required. A recent randomized trial [29] showed that neurocognitive robotic-assisted training of the hand improves motor ability, and is noninferior compared to traditional dose-matched neurocognitive therapy. Furthermore, in a controlled pilot study, ref.…”
Section: Robotic Assisted Therapy In Post-stroke Recoverymentioning
confidence: 99%